A corpus-based analysis of trends and themes of diabetes a case study of an online Malaysian newspaper - Afendi, Hamat; Azhar, Jaludin; Haslina, Rani; Ruhil Amal, Azmuddin; Aznida Firzah, Abdul Aziz; Tuti Ningseh, Mohd Dom (Teikyo University School of Medicine, 2023)
This paper presents the findings of an exploratory study that investigates the trends and themes related to the word 'diabetes' in the Malaysian media. The study utilizes the Malaysian Diabetes Corpus (MyDC), a specialized corpus consisting of online newspaper articles published between 2013 and 2018. The analysis combines corpus linguistics methodology with visualizations to examine the data. The results reveal a notable peak in the usage of the term 'diabetes' during the month of November across the studied years (2013-2018), coinciding with the increased attention given to World Diabetes Day. While there was a significant rise in the number of articles in 2018, the relative frequency of the word 'diabetes' remained stable throughout all the years. Among the various themes associated with 'diabetes', the most common ones include 'Awareness/Management', 'Type of (other related) disease', and 'Patient/Population'. This suggests that diabetes is increasingly portrayed in diverse contexts, with a greater emphasis on raising awareness and managing the condition rather than the traditional linguistic definition of the illness. The findings underscore the influential role of online media in promoting diabetes awareness and providing an effective platform for public diabetes prevention strategies. However, further investigation into the dynamics of online media and its impact on diabetes education is recommended to gain a deeper understanding of this relationship.